Silencing of SCEL promotes progression of oral squamous cell carcinoma via activating TGF-β/Smad pathway - Danping Li; Limei Li; Shu Wu; Jun Zhao; Haishan Zhang; Qiaoli Chen; Yingxi Mo; Liudmila Matskova; Ping Li; Xiaoying Zhou (Discover Oncology)
Abstract Objective SCEL serves as a precursor protein for the cornified envelope (CE), and its abnormal expression has been identified in various malignancies. Despite this, the functional role and detailed mechanisms of SCEL in oral squamous cell carcinoma (OSCC) remain to be clarified. Methods mRNA and protein expression of SCEL in OSCC cell lines and patient tissues were examined by qRT-PCR and IHC. In vitro and in vivo experiments assessed SCEL's influence on proliferation, apoptosis, cell cycle, ROS production, migration, and invasion. Western blotting was used to analyze SCEL’s effect on various signaling pathways, and a dual-luciferase reporter assay identified the miRNA that targets SCEL. Results SCEL is downregulated in OSCC, which correlates with reduced tumor cell differentiation and lymph node metastasis. SCEL inhibits OSCC proliferation, induces cell cycle arrest, apoptosis, and ROS production. SCEL suppresses the TGF-β/Smad pathway, inhibiting migration and invasion. SCEL also triggers MET and downregulates VEGFC, reducing lymph node metastasis probability. miR-5696 inhibitor effectively inhibits OSCC proliferation and invasion by targeting SCEL. Conclusion SCEL acts as a tumor suppressor in OSCC, influencing its progression and potential metastasis. Loss of SCEL facilitates OSCC progression by activating TGF-β/Smad signaling. Upregulating SCEL and silencing miR-5696 hold therapeutic promise for OSCC.